PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI PERKALIAN SISWA KELAS III SD NEGERI 067093 MEDAN T.A 2018/2019 - Anna Elena Simamora; Ruth Eleonora Donda Panggabean Eleonora Donda Panggabean (Jurnal Mutiara Pendidikan Indonesia, 2019)
This research is aimed to figure out the influences the effect of Numbered Head Together (NHT) and how The student’s result of mathematics studies by using cooperative learning type Numbered Heads Together ( NHT ) compared with students who use conventional learning. Based on the result the student’s research which was taught by the model of cooperative learning type Numbered Heads Together ( NHT ), the average score of the students’ study result was higher than the student of studied with conventional learning. This was found from the average score of experiment class It proved that there was significant influence by applying cooperative learning type Numbered Heads Together ( NHT ) to the students’ result of mathematics learning which could be known from the result of calculation, test – t > t table ( 4,305 > 2,000 ) with decibel calculation ( db) = 49, significant value = 0,05. Therefore Ho was rejected and Ha was accepted. It meant that the students’ average study result of learning mathematics in experiment class was different with be control.